2017
DOI: 10.1016/j.jclepro.2016.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant menu design and more responsible consumer food choice: An exploratory study of managerial perceptions

Abstract: The restaurant sector imposes substantial impacts on the environment and society. A large share of the sector's negative impacts is attributed to irresponsible consumer choice. To enhance sustainability of food service provision, consumer choice ought to be architected to make it more responsible. Restaurant menu can be (re-)designed to inform customers about the environmental and societal implications of their choice and thus 'nudge' selection of more benign food options. This study explores managerial opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 76 publications
4
62
0
4
Order By: Relevance
“…Second, despite the low level of public environmental awareness in Poland, the survey recorded consumer preference for local and sustainably-produced (which embeds methods of organic production and ethical animal husbandry) food when dining out with a subsequent desire to see these attributes displayed on a menu. This is in line with previous studies conducted on this topic in the western context (Edwards-Jones 2010; Filimonau and Krivcova 2017;Sims 2009). The key difference is however in that the Polish consumers have limited knowledge of how food provenance and the methods of food production are connected with the overall sustainability of restaurant food choice (Niewczas 2013).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, despite the low level of public environmental awareness in Poland, the survey recorded consumer preference for local and sustainably-produced (which embeds methods of organic production and ethical animal husbandry) food when dining out with a subsequent desire to see these attributes displayed on a menu. This is in line with previous studies conducted on this topic in the western context (Edwards-Jones 2010; Filimonau and Krivcova 2017;Sims 2009). The key difference is however in that the Polish consumers have limited knowledge of how food provenance and the methods of food production are connected with the overall sustainability of restaurant food choice (Niewczas 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This is reflected in the increased attention paid by consumers to the nutritional and calorific values of restaurant food (Gallicano et al 2012;Hoefkens et al 2012;Hwang and Lorenzen 2008). The precise impact of personal health considerations on restaurant food choice has not however been established (Filimonau and Krivcova 2017). Systematic literature reviews (Kiszko et al 2014;Long et al 2015;Swartz et al 2011) have provided contradictory evidence on the effect of the nutritional and calorific labels on restaurant food choice which calls for more research on this topic (Kim et al 2013), especially outside North America where the bulk of research on this topic was conducted.…”
Section: Health and Environmental Considerations As The Drivers Of Rementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, familiar food names and ingredients arouse negative valence emotions, such as boredom and calm. Filimonau and Krivcova (2017) mentioned that while restaurateurs acknowledged rising customer awareness about the changing food choice on personal health and the environment, but they were not confident about the use of menu design as a means to positively affect consumer choice. Kim et al (2016) study revealed that the number of online reviews customers had a significant positive impact on restaurant performance.…”
Section: Restaurant Selection Criteriamentioning
confidence: 99%
“…Por outro lado, da parte do consumidor, observa-se a procura de produtos mais equilibrados do ponto de vista nutricional (Huang, Wu, Lu, Shyu & Wang, 2017;Stranieri, Riccci & Banterle, 2017;Machín, Aschemann-Witzel, Curucthet, Giménez & Ares, 2018), mas que mantenham as suas propriedades gastronómicas e sensoriais (Huang et al, 2017;KERRY GROUP, 2018;Ballco, Caputo & De-Magistris, 2018). Ainda que, talvez não de um modo generalizado, temos atualmente um consumidor cada vez mais exigente, que procura estar informado das suas escolhas alimentares, mas cujo ritmo de vida e falta de tempo dificultam as escolhas alimentares saudáveis (Filimonau & Krivcova, 2017;Stranieri et al, 2017;). Outro fator que acresce a esta dificuldade é a oferta alimentar disponível, repleta de fast-food, alimentos processados e industrializados.…”
Section: Introductionunclassified